Tripodal gold(i) polypyridyl complexes and their Cu+ and Zn2+ heterometallic derivatives. Effects on luminescence. Issue 41 (15th October 2020) - Pinto, Andrea; Spigolon, Giulia; Gavara, Raquel; Zonta, Cristiano; Licini, Giulia; Rodríguez, Laura
Abstract : Tripodal Au(i ) complexes of tris(2-pyridylmethyl)amine coordinated to Au–PR3 moieties with open or cage-like structures have been synthesized and the changes on their resulting luminescence upon coordination to Zn 2+ and Cu + -salts analyzed. Abstract : Three gold(i ) tripodal complexes containing the tris(2-pyridylmethyl)amine (TPA) ligand coordinated to Au–PR3 moieties (PR3 = 1, 3, 5-triaza-7-phosphatricyclo[3.3.1.13.7]decane, PTA (1 ), 3, 7-diacetyl-1, 3, 7-triaza-5-phosphabicyclo[3.3.1]nonane, DAPTA (2 ) and triphenylphosphane (3 )) were prepared together with a cage-like structure containing triphosphane 1, 1, 1-tris(diphenylphosphinomethyl)ethane (4 ). The luminescence of these complexes has been studied and they show a red shift upon the formation of heterometallic complexes by reaction with Zn(NO3 )2, CuCl and [Cu(CH3 CN)4 ]BF4 . The different coordination motifs of the Zn 2+ and Cu + heterometallic species and the resulting changes in the recorded absorption, emission and NMR spectra were analysed and supported by TD-DFT calculations.